High resolution μCT of a mouse embryo using a compact laser-driven betatron source - Cole, JM; Symes, DR; Lopes, NC; Wood, JC; Poder, K; Alatabi, S; Botchway, S; Foster, PS; Gratton, S; Johnson, S; Kamperidis, C; Kononenko, O; et al. (National Academy of Sciences, 2018)
In the field of X-ray microcomputed tomography (µCT) there is a growing need to reduce acquisition times at high spatial resolution (approximate micrometers) to facilitate in vivo and high-throughput operations. The state of the art represented by synchrotron light sources is not practical for certain applications, and therefore the development of high-brightness laboratoryscale sources is crucial. We present here imaging of a fixed embryonic mouse sample using a compact laser–plasma-based X-ray light source and compare the results to images obtained using a commercial X-ray µCT scanner. The radiation is generated by the betatron motion of electrons inside a dilute and transient plasma, which circumvents the flux limitations imposed by the solid or liquid anodes used in conventional electron-impact X-ray tubes. This X-ray source is pulsed (duration <30 fs), bright (>1010 photons per pulse), small (diameter <1 µm), and has a critical energy >15 keV. Stable X-ray performance enabled tomographic imaging of equivalent quality to that of the µCT scanner, an important confirmation of the suitability of the laserdriven source for applications. The X-ray flux achievable with this approach scales with the laser repetition rate without compromising the source size, which will allow the recording of high-resolution µCT scans in minutes.